Phantom Limb Pain on Post-Surgical Amputation Osteosarcoma Children Patient - Bagus Pratama; Jason Mikail Amper; Gatra Hadimuti Wibowo; Rogatianus Bagus Pratignyo (Majority, 2022)
Osteosarcoma is a musculoskeletal malignancy that often occurs in pediatric patients requiring multidisciplinary management. Management in the form of amputation surgery (limb-salvage surgery) with a combination of chemotherapy or radiotherapy. Post-amputation complications that are often experienced by patient is postsurgical pain. Persistent Postsurgical Pain (PPSP) in pediatric patients is influenced by risk factors such as age, gender, preoperative preparation (pain intensity, anxiety, pain efficacy), intraoperative measures (site of surgery, potential for nerve damage, administration of analgesia regimens, technique of anesthesia), and postoperative management. The incidence of PPSP in osteosarcoma postamputation patients is related to Phantom Limb Syndrome with varying incidence and duration. This syndrome is a phenomenon that often occurs after post-amputation procedures in the form of sensation (Phantom Limb Sensation) or pain (Phantom Limb Pain) due to loss of part of the body. Phantom Limb Pain (PLP) is an effect and complication that occurs after amputation surgery in pediatric osteosarcoma patients. The PLP pathomechanism is related to the interaction of the Central Nervous System (Cortical Remapping Theory and Proprioceptive Theory) and the Peripheral Nervous System (Dorsal Root Ganglia and nocireceptor stimulation). Management of PLP consists of neuropathic pain medications such as antidepressants, opioids, anticonvulsants, N-methyl-D-aspartate (NMDA) receptor antagonists and other anesthetic agents.